2016
DOI: 10.1016/j.jsps.2015.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and implementation of behavioral and educational tools that improves the patients’ intentional and unintentional non-adherence to cardiovascular medications in family medicine clinics

Abstract: We reported that implemented multifaceted tools targeting patients, provider and healthcare system have improved the adherence to cardiovascular medications. Our interventions managed to improve patients' clinical outcome via improving adherence to prescribed cardiovascular medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…Direct methods include pill counting, reminder packaging, mobile health, electronic medication monitoring, measurement of drug concentrations in bodily fluids, etc. [12][13][14][15][16][17][18] Indirect methods mainly include self-reported questionnaires and scales. Although each available method has its own advantages and disadvantages, the self-reported method is the the most commonly used method to assess adherence behaviors, because it is economical and simple to gather information.…”
Section: Introductionmentioning
confidence: 99%
“…Direct methods include pill counting, reminder packaging, mobile health, electronic medication monitoring, measurement of drug concentrations in bodily fluids, etc. [12][13][14][15][16][17][18] Indirect methods mainly include self-reported questionnaires and scales. Although each available method has its own advantages and disadvantages, the self-reported method is the the most commonly used method to assess adherence behaviors, because it is economical and simple to gather information.…”
Section: Introductionmentioning
confidence: 99%
“…There are various ways used to assess adherence behaviors in hypertensive patients, which are divided into subjective reports (eg, questionnaire, inquiry), as well as indirect objective methods (eg, reminder packaging, mobile health, electronic medication monitoring). [813] However, self-reporting methods, which have the advantages of low cost and being the simplest way to gather information, are the most commonly used methods to assess adherence behaviors. [14] There are a variety of self-reported questionnaires that have been used to measure adherence behaviors in hypertensive patients [1518] ; each of these has its own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it becomes imperative to clarify the advantages of the therapeutic process for glycemic control in order to avoid clinical emergencies and undesirable hospitalizations, high costs to the health system and negative adverse effects. Additionally, studies show the level of schooling, advanced age, absence or diminution of visual acuity and functional loss as factors that hinder the application of insulin (23)(24)(25)(26) .…”
Section: Discussionmentioning
confidence: 99%
“…A prospective and developed cohort study in the United Arab Emirates, which used sessions of educational interventions to promote adherence to medication, showed satisfactory results in patients who did not adhere to the use of medications (24) . Another exploratory study using short message service focused on positive results related to insulin administration in young adults with 1DM found that after two weeks of intervention, participants increased adherence to insulin therapy (13) .…”
Section: Beliefs Related To Insulin Use In People With Type 2 Diabetementioning
confidence: 99%